2008
DOI: 10.1038/sj.leu.2405087
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of bortezomib in patients with renal impairment: results from the APEX phase 3 study

Abstract: Renal impairment is associated with poor prognosis in multiple myeloma (MM). This subgroup analysis of the phase 3 Assessment of Proteasome Inhibition for Extending Remissions (APEX) study of bortezomib vs high-dose dexamethasone assessed efficacy and safety in patients with relapsed MM with varying degrees of renal impairment (creatinine clearance (CrCl) o30, 30-50, 51-80 and 480 ml min À1). Time to progression (TTP), overall survival (OS) and safety were compared between subgroups with CrCl p50 ml min À1 (se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
99
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 165 publications
(112 citation statements)
references
References 33 publications
10
99
2
1
Order By: Relevance
“…The combination of cyclophosphamide, bortezomib, and dexamethasone induced ORR in up to 75% of refractory or relapsed MM patients [15]. Thalidomide and bortezomib maintained their high efficacy and acceptable toxicity profile in patients with renal impairment [19,20].…”
Section: Discussionmentioning
confidence: 94%
“…The combination of cyclophosphamide, bortezomib, and dexamethasone induced ORR in up to 75% of refractory or relapsed MM patients [15]. Thalidomide and bortezomib maintained their high efficacy and acceptable toxicity profile in patients with renal impairment [19,20].…”
Section: Discussionmentioning
confidence: 94%
“…Clinical trials have demonstrated that carfilzomib and bortezomib are clinically active regardless of the degree of renal insufficiency in patients (Jagannath et al , 2005; San‐Miguel et al , 2008; Badros et al , 2013). Consistent with this, we found that carfilzomib induces consistent and potent inhibition of multiple proteasomal active sites in MM patients, regardless of patient renal function.…”
Section: Discussionmentioning
confidence: 99%
“…[60][61][62] In the SUMMIT and CREST trials, bortezomib treatment was found to lead to an overall response rate of 25 and 30% in patients with moderate and severe renal impairment, respectively, 65 whereas the toxicity was comparable to that of patients without renal impairment. In a subanalysis of the APEX trial, bortezomib was effective in patients with renal impairment, including those with severe renal impairment, 66 with response rates and time to response similar across all subgroups of patients with varying degrees of renal function. Time to progression and overall survival were not substantially affected in patients with severe to moderate renal impairment compared to those with no or mild renal impairment or to the overall APEX population.…”
Section: Bortezomibmentioning
confidence: 99%